ANALISIS PERAMALAN PENJUALAN SUSU FORMULA DI TOKO SUSU TY-SYAR DENGAN MENGGUNAKAN METODE MOVING AVERAGE - Muhammad Syahrul Romadhon; Rifky Tri Nugroho; Yossie Saputra; Paduloh Paduloh (Jurnal Salome : Multidisipliner Keilmuan, 2024)
Ty-Syar milk shop is a shop that sells formula milk. This milk shop wants to forecast sales for the next year. The aim of this research is to determine the sales forecast for formula milk. The method used to find out sales forecasting uses the Moving Average. The results of this research using Moving Average obtained MAPE 2,691, MAD 21,852, MSD 741,975. So the average obtained using the Sigle Moving Average is 775, this is the average value of the movement of milk sales during 2022.